2023
DOI: 10.1245/s10434-022-13064-0
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Sentinel Lymph Node Dissection in Patients with a Preoperative Diagnosis of Ductal Cancer In Situ by Preoperative Injection with Superparamagnetic Iron Oxide (SPIO) Nanoparticles: The SentiNot Study

Abstract: Background Difficulty in preoperatively assessing the risk for occult invasion or surgery that precludes future accurate axillary mapping in patients with ductal cancer in situ (DCIS) account for overutilization of SLND. Methods Prospective, multicenter, cohort study, including women with any DCIS planned for mastectomy or DCIS grade 2 and > 20 mm, any DCIS grade 3, any mass-forming DCIS and any planned surgery. Patients received an interstitial SPIO in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The median magnetic count was lower for ‘all SLN’, but not for the ‘first SLN’, and the values allowed for easy detection. These data not only corroborate previous reports and meta-analyses regarding SPIO as a tracer for SLN after PST 1 , 20 but suggest that the concept of delayed SLND through a wide time frame between SPIO administration and SLND, introduced in the SentiNot study 2 , 3 , can be applicable in the setting of PST, facilitating logistics and potentially enhancing axillary mapping.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The median magnetic count was lower for ‘all SLN’, but not for the ‘first SLN’, and the values allowed for easy detection. These data not only corroborate previous reports and meta-analyses regarding SPIO as a tracer for SLN after PST 1 , 20 but suggest that the concept of delayed SLND through a wide time frame between SPIO administration and SLND, introduced in the SentiNot study 2 , 3 , can be applicable in the setting of PST, facilitating logistics and potentially enhancing axillary mapping.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, SPIO provide the possibility for delayed SLND, as demonstrated in the SentiNot study. In that study, SLND using SPIO was still feasible weeks after primary breast surgery for ductal carcinoma in situ , in the cases where specimen pathology demonstrated invasive cancer 2 , 3 . However, the role of SPIO for SLND after primary systemic therapy (PST) has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 94%
“…They reported that the technical success rate of repeat SLNB, although not statistically significant, was higher in the primary mastectomy group (67.7%) than in the primary lumpectomy group (59.7%) ( p = 0.050) and significantly higher in the primary no-axillary procedure group (84.9%) than in the primary SLNB group (75.7%) ( p < 0.001). Karakatsanis et al [ 33 ] reported that using nanoparticles to mark the SLN allows for accurate delayed SLNB, if warranted. Hence, axillary surgery in DCIS may be necessary in cases of diagnostic upgrading; however, unnecessary axillary surgery can be avoided by delaying SLNB after the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been reports of successful and technically feasible SLNB after mastectomy, index surgery is the best chance to assess axillary lymph nodes due to the disruption of lymphatic channels [ 18 , 21 ]. Recently, the SentiNot trial showed that marking the SLN with superparamagnetic iron oxide in patients with a preoperative diagnosis of DCIS resulted in avoiding upfront SLNB in 78.3% of patients, with delayed SLNB being feasible and yielding high detection rates once the invasive disease was found [ 22 ].…”
Section: Discussionmentioning
confidence: 99%